Does pelvic orientation influence wear measurement of the acetabular cup in total hip arthroplasty—an experimental study - Wu, Junzhe; Taylor, Dominic; Forst, Raimund; Seehaus, Frank (Applied Sciences, 2021)
Roentgen stereophotogrammetric analysis (RSA) is the gold standard to detect in vivo material wear of the bearing couples in hip arthroplasty. Some surgical planning tools offer the opportunity to detect wear by using standard a.p. radiographs (2Dwear ), whilst RSA (3Dwear ) needs a special radiological setup. The aims of this study are to prove the interchangeable applicability of a 2Dwear approach next to RSA and to assess the influence of different pelvic positions on measurement outcomes. An implant-bone model was used to mimic three different wear scenarios in seven pelvic-femur alignment positions. RSA and a.p. radiographs of the reference and a follow-up (simulated wear) pose were acquired. Accuracy and precision were worse for the 2Dwear approach (0.206 mm; 0.159 mm) in comparison to the 3Dwear approach (0.043 mm; 0.017 mm). Changing the pelvic position significantly influenced the 2Dwear results (4 of 7, p < 0.05), whilst 3Dwear results showed almost no change. The 3Dwear is superior to the 2Dwear approach, as it is less susceptible to changes in pelvic position. However, the results suggest that a 2Dwear approach may be an alternative method if the wear present is in the range of 100–500 µm and a.p. radiographs are available with the pelvis projected in a neutral position.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Accuracy; Pelvic orientation; Polyethylene wear; Precision; Roentgen stereophotogrammetric analysis; Total hip arthroplasty